0474 Three-arm randomised controlled trial of Cognitive Behavioural Therapy for Insomnia, a responsive bassinet, and sleep hygiene for preventing postpartum insomnia: Preliminary findings on maternal insomnia and sleep outcomes (Study for Mother-Infant Sleep). (25th May 2022) - Quin, Nina; Tikotzky, Liat; Astbury, Laura; Stafford, Lesley; Fisher, Jane; Wiley, Joshua; Bei, Bei
Abstract: Introduction: Insomnia symptoms are common during the perinatal period and are linked to adverse parent/infant outcomes. This single-blind 3-arm randomised controlled trial examined how two interventions targeting different mechanisms prevent postpartum insomnia compared to sleep hygiene control. Trial registration: ACTRN12619001166167. Methods: Participants were nulliparous females 26-32 weeks gestation with self-reported insomnia symptoms (Insomnia Severity Index [ISI] scores ≥ 8). Participants were randomized 1:1:1 to: (a) a responsive bassinet designed to support infant sleep until 6 months postpartum (RB), (b) therapist-assisted cognitive behavioural therapy for insomnia (CBT-I) delivered during pregnancy and postpartum, or (c) a sleep hygiene booklet (control condition; CTRL). Outcomes were assessed at baseline (T1), 35-36 weeks gestation (T2), and 2, 6, and 12 months postpartum (T3-T5). The primary outcome is ISI scores averaged T3-T5. Secondary outcomes are PROMIS Sleep Disturbance (SDI), Sleep-Related Impairment (SRI), and self-report total sleep time (TST). We report preliminary results on T1-T4 as T5 is ongoing. Multiple regression analyses controlling for baseline outcomes examined group differences at post-baseline timepoints. Results: 127 participants were randomised (age M±SD=32.62±3.49; RB = 44, CBT-I = 42, CTRL = 41), and 118 (92.9%) completed T4. Compared to CTRL, CBT-I had lower ISI, SDI, and SRI at T2, T3, and T4 (all p<.05 except p=.07 and .06 for ISI at T3 and T4; Cohen's d ranges 0.39-0.99); differences in TST were non-significant at all timepoints (all p>.25). The RB condition had significantly longer TST at T4 (40.10 min longer, p=.008, d=.63) compared to CTRL, but these two conditions did not differ significantly on any other measures across all timepoints (p>.22). Conclusion: Preliminary findings suggest CBT-I was efficacious in preventing insomnia symptoms and reducing sleep disturbance and sleep-related impairment, but did not increase maternal sleep duration postpartum. Conversely, a responsive bassinet designed to support infant sleep meaningfully increased maternal sleep duration at 6 months postpartum but did not prevent insomnia symptoms. These initial findings suggest that perinatal sleep complaints are a multifactorial problem that likely require multi-component interventions targeting different causes and mechanisms. Support (If Any): National Health and Medical Research Council, Department of Education and Training.